Ion toxicity in waterlogged soils: mechanisms of root response and adaptive strategies - Zhang, Lin; Li, Yan; Wang, Yanqin; Liu, Zhaohui; Kronzucker, Herbert J.; Wang, Zhaoyue; Shi, Weiming; Li, Guangjie (Frontiers in Plant Science, 2025)
Waterlogging poses a significant global threat to agriculture by inducing ion toxicities (e.g. Fe²+, Mn²+, NH4+) in roots due to soil redox changes. This review synthesizes current insights into how plant roots, particularly in Arabidopsis, respond to these toxicities, focusing on root system architecture (RSA) modifications and underlying mechanisms. Under waterlogging, soil redox changes drive Fe²+ and Mn²+ accumulation in reducing layers, while NH4+-based fertilizers elevate NH4+:NO3- ratios. NH4+ inhibits primary root (PR) elongation by disrupting cell division and energy metabolism via VTC1 and LPR2 genes, while locally stimulating lateral root (LR) formation through pH-dependent auxin diffusion. Ethylene and NO signaling interact to modulate gravitropism via PIN2 and ARG1/GSA1 pathways. Fe toxicity arrests PR growth by reducing cell activity in the root tip, involving ethylene, ROS (H2O2/O2-), and NO pathways. GSNOR emerges as a key gene for Fe tolerance, balancing NO homeostasis. LR formation under Fe stress relies on PIN2/AUX1-mediated auxin transport and ferritin storage, with ROS-auxin crosstalk influencing adaptive responses. Mn toxicity inhibits PR elongation by repressing auxin biosynthesis (YUC genes) and efflux (PIN4/PIN7), while miR781 and cation transporters (CAX4, MTP11) facilitate detoxification. Vacuolar compartmentation and Ca²+ signaling via ECA proteins are also critical. Despite progress, key gaps remain: identifying ion sensors in root tips, extrapolating findings to long-lived species, modeling multi-ion interactions under dynamic waterlogging conditions, and establishing real-time root signal monitoring systems. Integrating temporal and environmental factors (e.g. temperature) will enhance understanding of RSA reprogramming for waterlogging tolerance.